Associations between demographic, clinical, and socioeconomic factors and mental health in long COVID: A clinic-based cross-sectional study - Anh N.Q. Pham; Julia Smith; Kaylee A. Byers; Kiffer G. Card (PLoS ONE, 2026)
Background Long COVID is associated with persistent symptoms, including the onset of new mental health challenges such as anxiety and depression, as well as the worsening of pre-existing conditions. While previous research has examined the impact of demographic factors, chronic conditions, and traumatic events on mental health, little is known about how these factors interact to shape mental health outcomes in individuals with Long COVID. This study investigates the relationship between selected demographics characteristics, social determinants of health – specifically living settings, place of living, employment status, and working hours – and chronic health conditions on mental health outcomes among individuals with Long COVID. Methods This is a secondary analysis using previously collected survey data from 3,611 individuals, who were diagnosed, referred to and admitted at Post-COVID Recovery Clinics, British Columbia, Canada at the time of their admission. The dataset includes demographic variables (sex, age, living situation, employment status, occupation, ethnicity), history of chronic conditions, and mental health outcomes (anxiety and depression) of patients. Univariable and multivariable Generalized Linear Regression analyses were conducted to examine associations between SDoH and mental health outcomes, adjusting for potential confounders. Results The cohort had a mean age of 50 years, and 62% of participants were female. Overall, 38% screened positive for anxiety, 35% for depression, and 26% for both conditions following COVID-19 infection. In multivariable analyses, younger age, cognitive issues, and activity limitations were significantly associated with symptoms of anxiety, while younger age, cognitive issues, and physical impairments were significantly associated with symptoms of depression. In the multivariable model, individuals with cognitive issues were more likely to report anxiety (RR = 1.45, 95% CI: 1.34–1.56) and depression (RR = 1.54, 95% CI: 1.42–1.68). Activity limitations were also associated with anxiety (RR = 1.12, 95% CI: 1.01–1.24), and physical impairments with depression (RR = 1.43, 95% CI: 1.24–1.65). Overall, 38% of patients reported symptoms of anxiety, 35% reported depression, and 26% experienced both following COVID-19 infection. Conclusion These findings highlight important associations between mental health symptoms and clinical factors among individuals with Long COVID and underscore the need for further longitudinal research to clarify causal pathways and inform mental health support strategies, particularly among those with activity limitations, cognitive and physical impairments. Patient or public contribution The data collection and questionnaire were designed and conducted by the Post-COVID Integrated Clinic Network in British Columbia, Canada.